Management of classical Islamic education - Leni Martha Karisma; Joko Sutarto; Tri Suminar (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2019)
The purpose of this research is to describe the planning, organizing, implementing, and evaluating of classical Islamic education at Kuttab Al Fatih Semarang. This research uses a qualitative approach. Data collection with observation methods, documentation studies and interviews. The validity of data with extended entry techniques, observational diligence techniques, and triangulation techniques. The results showed the management of classical Islamic education in Kuttab Al Fatih Semarang ranging from planning, organizing, implementation, and evaluation done in accordance with the concept of Islam in the heyday of Islam that aspires to build Quality generation. The management of the classical Islamic education in Kuttab Al Fatih is very effective to create students who want to have a character of faith, to be the memorization of the Qur'an, deepen the miracle of the Qur'an, mastering the language of civilization and have the skills of life.